Gold-Catalyzed Cross-Coupling and 1,2-Difunctionalization Reactions: A Personal Account - Ambegave, Shivhar B.; Patil, Nitin T. (Synlett, 2022)
In recent years, gold catalysis involving Au(I)/Au(III) redox cycle has gained significant attention. This account summarizes our contributions to the development of Au(I)/Au(III) catalysis, focusing on cross-coupling reactions and 1,2-difunctionalization reactions of C–C multiple bonds. A special emphasis has been given to understanding the mechanism of the reactions.1 Introduction2 Gold-Catalyzed Cross-Coupling Reactions3 Gold-Catalyzed 1,2-Difunctionalization of C–C Multiple Bonds4 Conclusion and Outlook
Keywords: biaryls; catalysis; cross-coupling; cyclisation; enantioselectivity; ligands